Artificial Intelligence Applicability in the Pharmaceutical Industry: Present Perspectives and Future Formations. - Hasan, Maimuna; Lamem, Md. Faiazul Haque; Sahid, Muaj Ibne; Sarker, Md. Rifat (Inquiry (00469580), 2026)
Artificial intelligence (AI), like ChatGPT, Microsoft copilot, and Google Gemini, is transforming pharmaceutical research, production, and healthcare delivery. Despite global adoption, the level of AI awareness, readiness, and application among pharmaceutical professionals remains unclear. This study aimed to evaluate the awareness, knowledge, attitudes, and perceptions of AI among pharmaceutical professionals and to identify factors influencing its adoption. A cross-sectional survey was conducted among professionals from various pharmaceutical sectors using a structured online questionnaire. Descriptive statistics were applied to analyze demographic characteristics, AI familiarity, usage, and perceptions. Most respondents (81.8%) were aware of AI, but only 2.3% reported extensive familiarity. ChatGPT was the most frequently used AI tool (63.6%), while only 27.3% reported organizational adoption. Support for AI adoption was high (86.4%), yet only 22.7% considered the industry fully ready. Perceived benefits included improved efficiency (86.4%) and quality (70.4%), while major concerns involved automation dependency (36.4%) and implementation costs (34.1%). Pharmaceutical professionals show strong interest in AI despite limited organizational readiness and formal training. Structured education, regulatory guidance, and ethical frameworks are critical for effective AI integration in the sector.